HAZF HURUF NIDA يا PADA LAFADZ DOA MENGGUNAKAN KATA ربّ DALAM ALQURAN - Saputra, Indra; Sa'adiyah, Hurriyatus (STAI Darul Quran Payakumbuh, 2022)
Prayer is a worship that is highly recommended in Islam, in the rules of the Arabic language there is a special letter that is used for prayer, namely the letter يا, this letter is called the letter nida. In some verses this letter is not written down or mazuf. In addition to the rules of language, the reason for the removal of the nida letter is also a reason in terms of balaghah, which states the closeness of Allah to His servants. This research method uses a descriptive and analytical library research approach. The main sources for this research are Arabic grammar books and other supporting Arabic language books.